Entrenchment : wealth, power, and the constitution of democratic societies - Starr, Paul (Yale University Press, 2019)
An investigation into the foundations of democratic societies and the ongoing struggle over the power of concentrated wealth Much of our politics today, Paul Starr writes, is a struggle over entrenchment--efforts to bring about change in ways that opponents will find difficult to undo. That is why the stakes of contemporary politics are so high. In this wide ranging book, Starr examines how changes at the foundations of society become hard to reverse--yet sometimes are overturned. Overcoming aristocratic power was the formative problem for eighteenth century revolutions. Overcoming slavery was the central problem for early American democracy. Controlling the power of concentrated wealth has been an ongoing struggle in the world's capitalist democracies. The battles continue today in the troubled democracies of our time, with the rise of both oligarchy and populist nationalism and the danger that illiberal forces will entrench themselves in power. Entrenchment raises fundamental questions about the origins of our institutions and urgent questions about the future.